Efficacy of Colchicine and Budesonide in Improvement Outcomes of Patients with Coronavirus Infection 2019 in Damascus, Syria: A Randomized Control Trial - Alsultan, Mohammad; Obeid, Ameer; Alsamarrai, Omar; Anan, Mohamed Taher; Bakr, Aliaa; Soliman, Nawwar; Kurdy, Mamdoh; Mosa, Muhannad Hag; Saleh, Zain; Hujij, Fatima; Barhoum, Jafar (Interdisciplinary Perspectives on Infectious Diseases, 2021)
COVID-19 was reported in China in 2019 and has spread worldwide. Transmission occurs through respiratory secretions and, less commonly, through contaminated surfaces. The severity of the disease can range from asymptomatic to acute respiratory distress syndrome (ARDS). In this study, we aim to investigate the efficacy of two agents (oral colchicine and budesonide inhaler) in COVID-19 infection management, compared with supportive care alone. 77 patients were admitted to the isolation section of Al Assad University Hospital, between the 1st of August and the 30th of August. A total of 49 patients were included in this randomized control trial, after excluding ineligible patients. The random sample was divided into three groups; the first group was supportive care plus colchicine, the second group was supportive care plus budesonide inhaler, and the control group was supportive care alone. PaO2/FiO2 was improved in the budesonide group, higher than the supportive and colchicine groups. The median hospitalization days were shorter when using colchicine or budesonide, opposed to supportive care alone (8 vs 10 days, respectively). 34 patients (69.3%) were discharged, and 27 patients (55.1%) were followed up until they were weaned from oxygen and made a complete recovery. There was a significant decrease in mortality with colchicine (3 patients; 21.4%) compared with supportive care (7 patients; 33.3%) and the budesonide group (5 patients; 35.7%).